Zinc-based coordination polymer based on heterocyclic ligand as well as preparation method and application of zinc-based coordination polymer

By designing a zinc-based coordination polymer Zn-PTZpy based on heterocyclic ligands, the biotoxicity problem of Cd-MOF was solved, and high-sensitivity detection of S2O42- and CrO42- was achieved, expanding the applications of biosensing and imaging.

CN121405964AActive Publication Date: 2026-01-27JIANGXI NORMAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511604256.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-05
Publication Date
2026-01-27
Estimated Expiration
2045-11-05

AI Technical Summary

Technical Problem

The application of existing cadmium-based metal-organic framework (Cd-MOF) fluorescent sensors in biological systems is limited by the biotoxicity of the Cd metal center, and existing fluorescent sensors have insufficient sensitivity and selectivity when detecting hexavalent chromium ions and ascorbic acid.

Method used

Using a zinc-based coordination polymer based on heterocyclic ligands, a Zn-PTZpy material with excellent luminescence properties was constructed by designing the phenothiazine derivative ligand 3,7-bis(4-pyridyl)phenothiazine to coordinate with zinc ions, which was then used to detect S2O42- and CrO42-.

Benefits of technology

It achieves high sensitivity and selectivity in the detection of S2O42- and CrO42-, broadening the application prospects of the material in fields such as biosensing and imaging. The fluorescence response is significant and rapid, and the enhancement or quenching effect is significant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121405964A_ABST
    Figure CN121405964A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fluorescence sensing, and particularly relates to a zinc-based coordination polymer based on a heterocyclic ligand and a preparation method and application thereof. The method comprises the following steps: dissolving 3, 7-dibromo-10H-phenothiazine, pyridine-4-boric acid and K2CO3 in a mixed solution of DMF (Dimethyl Formamide) and H2O, uniformly stirring, then adding tetrakis (triphenylphosphine) palladium, carrying out a heating reflux reaction under protective gas, removing a solvent after the reaction is finished, separating impurities, and purifying to obtain 3, 7-bis (4-pyridyl) phenothiazine; the preparation method comprises the following steps: preparing a heterocyclic ligand, dissolving the heterocyclic ligand and zinc nitrate hexahydrate in a mixed solution of DMF and H2O, uniformly stirring, heating to react, and washing and drying after the reaction is finished to obtain the zinc-based coordination polymer based on the heterocyclic ligand. According to the present invention, by using the butterfly conformation and electron donating effect of the ligand molecule 3, 7-bis (4-pyridyl) phenothiazine and the coordination binding capacity synergistic effect of pyridine, the ligand molecule 3, 7-bis (4-pyridyl) phenothiazine is coordinated with zinc ions to construct the novel material with excellent luminescence property;
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of fluorescent sensing, and particularly relates to a zinc-based coordination polymer based on a heterocyclic ligand and a preparation method and application thereof. BACKGROUND

[0002] Phenothiazine (PTZ) has a non-planar "butterfly" structure, and due to its unique intramolecular charge transfer mechanism, it is often used as a near-infrared fluorescent dye with red-shifted fluorescence spectrum. According to the El-sayed rule, organic luminescent molecules containing heteroatoms (such as N and O) are selected, and the lone pair electrons of the heteroatoms help intersystem crossing, which is conducive to the generation of triplet excitons. Pyridyl ligands are organic molecules with pyridine ring structures, which are six-membered carbon-nitrogen heterocycles, and the nitrogen atom serves as a coordination site to form a stable coordination bond with metal ions. These ligands provide coordination sites and endow CPs with specific chemical functions, such as catalytic activity. The diversity and modifiability of pyridyl ligands provide extensive flexibility for designing CPs with customized properties.

[0003] Compared with other environmental pollutant detection methods such as voltammetry and atomic absorption spectrometry, the fluorescence analysis method has the advantages of short response time, low cost and simple operation in the process of environmental pollutant detection. Therefore, it is very meaningful to develop a fluorescence sensor that can detect. A fluorescence sensor based on a new three-dimensional Cd-MOF is developed in the prior art, which can realize high-sensitivity and high-selectivity detection of hexavalent chromium ions and ascorbic acid in "off-on" mode. Although the metal-organic framework (Cd-MOF) based on cadmium (Cd) has good luminescent properties, it is limited by the biological toxicity of the Cd metal center, and its application in actual biological systems faces major challenges. SUMMARY

[0004] The purpose of the present application is to solve the problems of the prior art, and to provide a zinc-based coordination polymer based on a heterocyclic ligand and a preparation method and application thereof. The following technical solutions are used: In a first aspect, the present application provides a preparation method of a zinc-based coordination polymer based on a heterocyclic ligand, comprising the following steps: Dissolve 3,7-dibromo-10H-phenothiazine, pyridine-4-boronic acid and K2CO3 in a mixed solution of DMF and H2O, stir uniformly, then add tetrakis(triphenylphosphine)palladium and perform heating reflux reaction under a protective gas, remove the solvent after the reaction is completed, separate impurities, purify, and obtain 3,7-di(4-pyridyl)phenothiazine; Dissolve the 3,7-di(4-pyridyl)phenothiazine and zinc nitrate hexahydrate in a mixed solution of DMF and H2O, stir uniformly, heat and react, wash after the reaction is completed, and dry to obtain the zinc-based coordination polymer based on the heterocyclic ligand.

[0005] The present application designs and synthesizes a novel phenothiazine derivative ligand 3,7-bis(4-pyridyl) phenothiazine (PTZpy), which can be coordinated with Zn 2+ through pyridine nitrogen sites to form a zinc-based coordination polymer Zn-PTZpy with excellent luminescent properties. 2- Based on the conjugation of phenothiazine fluorophore and pyridine group, a fluorescent sensor for detecting S2O4 2- and CrO4

[0006] As a further preferred embodiment, the molar ratio of 3,7-dibromo-10H-phenothiazine, pyridine-4-boronic acid, tetrakis(triphenylphosphine)palladium and K2CO3 is 1.4 mmol: 11.2 mmol: 0.07 mmol: 20 mmol.

[0007] As a further preferred embodiment, the molar ratio of 3,7-bis(4-pyridyl) phenothiazine and zinc nitrate hexahydrate is 0.025 mmol: 0.025 mmol.

[0008] As a further preferred embodiment, the temperature of the heating reflux reaction is 100℃-120℃, and the time is 48h-72h.

[0009] As a further preferred embodiment, the temperature of the heating reaction is 100℃-110℃, and the time is 24h-48h.

[0010] As a further preferred embodiment, the volume ratio of DMF and H2O in the mixed solution of DMF and H2O is 3-8:1.

[0011] As a further preferred embodiment, the impurity separation specifically comprises the following steps: After the reaction is completed, the product after removing the solvent is dissolved in a mixed solution of dichloromethane and water, the two phases are separated, the organic phase is washed, filtered and rotary evaporated.

[0012] In a second aspect, the present application provides a zinc-based coordination polymer based on a heterocyclic ligand prepared by the above preparation method.

[0013] In a third aspect, the present application provides a fluorescent probe comprising the zinc-based coordination polymer based on a heterocyclic ligand described above.

[0014] In a fourth aspect, the present application provides the use of the zinc-based coordination polymer based on a heterocyclic ligand described above or the fluorescent probe described above in detecting S2O4 2- and CrO4 2- .

[0015] The present application selects zinc (Zn 2+) as a metal center, fundamentally solves the biological toxicity problem, and significantly widens the application prospect of the material in the field of biosensing and imaging, etc. The coordination of zinc ions is carried out by using the butterfly conformation, electron-donating effect and coordination combination ability of the ligand molecule 3,7-di (4-pyridyl) phenothiazine. According to the experimental data of the application, the coordination polymer added into S2O4 2- solution can enhance the fluorescence of the mixture solution, and the enhancement degree can be more than 200%. The fluorescence quenching effect is generated in the CrO4 2- solution, and the quenching degree can be more than 90%. The titration experiment shows that the sensor has good sensitivity, selectivity and rapid response to S2O4 2- and CrO4 2- , and expands the application of the polymer in the field of biological labeling, etc.

[0016] The beneficial effects of the application are: By skillfully coupling the molecular characteristics of phenothiazine and pyridine, the application designs a new structure material, and accordingly constructs a fluorescence sensor with high selectivity and dual response function, which provides a new strategy for developing more functional CPs materials based on phenothiazine derivatives. The material has simple synthesis method, low raw material price, and also realizes the dual-function sensor for reducing (S2O4 2- ) and oxidizing (CrO4 2- ) anions, greatly improves the detection efficiency and application potential, and has good sensitivity, selectivity and rapid response to S2O4 2- and CrO4 2- , and can quickly identify S2O4 2- and CrO4 2- in actual polluted water samples, and expands the application of the polymer in the field of biological labeling, etc. BRIEF DESCRIPTION OF DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the application, the drawings used in the embodiments will be briefly introduced. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor.

[0018] Figure 1 The nuclear magnetic resonance hydrogen spectrum of PTZpy is shown.

[0019] Figure 2 The crystal structure diagram of Zn-PTZpy coordination polymer is shown; wherein, (a) is an asymmetric unit; (b-c) is a three-dimensional structure.

[0020] Figure 3 The photophysical properties of Zn-PTZpy coordination polymer are shown; (a) is the excitation spectrum of PTZpy at 397 nm emission wavelength and the emission spectrum at 519 nm excitation wavelength; (b) is the excitation spectrum of Zn-PTZpy at 397 nm emission wavelength and the emission spectrum at 593 nm excitation wavelength; (c) is the CIE coordinate diagram (the insert is the corresponding picture under the irradiation of 254 nm ultraviolet lamp); (d) is the lifetime decay curve of Zn-PTZpy.

[0021] Figure 4 The fluorescence sensing performance of Zn-PTZpy is shown; (a) is the fluorescence selective detection emission diagram of Zn-PTZpy and different compound mixtures; (b) is the fluorescence selective detection column chart of Zn-PTZpy and different compound mixtures.

[0022] Figure 5 The fluorescence intensity change diagram of Zn-PTZpy (a, c) is shown after gradually adding CrO4 2- / S2O4 2- solution to the Zn-PTZpy suspension; the Stern-Volmer (Stern-Volmer) diagram of Zn-PTZpy (b, d) is shown after gradually adding CrO4 2- / S2O4 2- solution to the Zn-PTZpy suspension.

[0023] Figure 6 The preparation schematic diagram based on the heterocyclic ligand zinc-based coordination polymer is shown. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.

[0025] Embodiment 1 A preparation method of a heterocyclic ligand zinc-based coordination polymer, which specifically comprises the following steps: (1) Preparation of 3,7-di(4-pyridyl)phenothiazine (PTZpy) ligand Dissolve 3,7-dibromo-10H-phenothiazine (500 mg, 1.4 mmol), pyridine-4-boronic acid (689 mg, 11.2 mmol) and K2CO3(2.72 g, 20 mmol) in DMF (80 mL) and H2O (10 mL), stir for 15 min, degas with nitrogen, then add tetra(triphenylphosphine)palladium (809 mg, 0.07 mmol) and heat to 100°C under nitrogen protection, heat to reflux for 72 h, after the reaction is completed, remove the solvent under vacuum to obtain the product; redissolve the product in a mixture of dichloromethane and water, separate the two phases, and wash the organic phase with water twice; filter and rotary evaporate the organic phase to obtain the crude product, then purify the crude product by silica gel column chromatography with dichloromethane and methanol as eluents to obtain 3,7-di(4-pyridyl)phenothiazine with a yield of 70.6%.

[0026] (2) Preparation of a heterocyclic ligand-based zinc-based coordination polymer (Zn-PTZpy) Dissolve 0.025 mmol of 3,7-di(4-pyridyl)phenothiazine (PTZpy) and 0.025 mmol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) in DMF (3 mL) and H2O (1 mL), stir for 5 min; then transfer the obtained solution into a reaction kettle, heat to 100°C in an oven, and react for 48 h; after the reaction is completed, wash with water three times, and then place in a 60°C vacuum drying box for drying for 24 h to obtain red crystals (Zn-PTZpy).

[0027] Characterize the 3,7-di(4-pyridyl)phenothiazine (PTZpy) ligand and the heterocyclic ligand-based zinc-based coordination polymer (Zn-PTZpy) prepared above, as follows: Figure 1 The figure shows the proton nuclear magnetic resonance spectrum of PTZpy; as can be seen from the figure, the final product is confirmed to be the target product by the proton nuclear magnetic resonance spectrum data. In addition to the N-H resonance of a broad singlet peak appearing at 9.10 ppm, 6 aromatic protons and 8 pyridyl group protons are accurately calculated in various integral traces, the shifts of the aromatic protons show doublet peaks at δ7.49, δ7.43, δ6.78, with an integral of 2H. The chemical shifts of the 8 protons of the pyridyl moiety clearly show doublet peaks at δ8.55, δ7.63, with an integral of 4H, which is consistent with the prediction.

[0028] Select a Zn-PTZpy coordination polymer crystal with a clean and smooth surface, no concave surface, and no cracks, and use a SuperNova E G8910B X ray single crystal diffractometer with a graphite monochromatic Mo The diffraction data were collected in a scan mode with K a (wavelength 0.71013 Å) radiation. All data were corrected by empirical absorption and the crystal structure was solved by direct method. The detailed crystal determination data are shown in Table 1, and the crystal structure is shown in Figure 2 .

[0029] Table 1 Crystallographic data of Zn-PTZpy The single crystal X-ray diffraction analysis of Table 1 shows that Zn-PTZpy is crystallized in the orthorhombic Pna21 space group. Figure 2 The single crystal structure of Zn-PTZpy can clearly see the spatial configuration of the butterfly type of the phenothiazine group. This non-planar structure effectively inhibits the π-π stacking interaction, which is conducive to improving the luminescent performance. The asymmetric unit is composed of two Zn 2+ cations, four PTZpy ligands. The Zn1 and Zn2 centers adopt a tetrahedral coordination geometry, which is four-coordinated by two N atoms from two pyridyl groups of the PTZpy ligand. In Zn1 and Zn2, four monodentate pyridyl groups connect two Zn centers to obtain a [Zn(C 12 H9NS-C 10 H8N2)2] unit. Finally, this one-dimensional chain is infinitely grown through hydrogen bonding to form a three-dimensional (3D) supramolecular structure.

[0030] Example 2 A preparation method of a zinc-based coordination polymer based on a heterocyclic ligand, which specifically comprises the following steps: (1) Preparation of 3,7-bis (4-pyridyl) phenothiazine (PTZpy) ligand The process is exactly the same as step (1) of Example 1 (2) Preparation of zinc-based coordination polymer (Zn-PTZpy) based on a heterocyclic ligand Dissolve 0.025 mmol of 3,7-bis (4-pyridyl) phenothiazine (PTZpy) and 0.02 mmol of zinc nitrate hexahydrate (Zn (NO3) 2·6H2O) in DMF (3 mL) and H2O (1 mL), stir for 5 min; then transfer the obtained solution into a reaction kettle, put it into an oven and heat to 100℃, react for 48 h; after the reaction is completed, wash with water for three times, and then put it into a 60℃ vacuum drying box and dry for 24 h to obtain a small amount of red crystals (Zn-PTZpy).

[0031] Example 3 A preparation method of a zinc-based coordination polymer based on a heterocyclic ligand, which specifically comprises the following steps: (1) Preparation of 3,7-bis(4-pyridyl)phenthiazine (PTZpy) ligand The process is exactly the same as step (1) in Example 1. (2) Preparation of zinc-based coordination polymer based on heterocyclic ligands (Zn-PTZpy) 0.025 mmol of 3,7-bis(4-pyridyl)phenthiazide (PTZpy) and 0.03 mmol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) were dissolved in DMF (3 mL) and H2O (1 mL) and stirred for 5 min. The resulting solution was then transferred to a reaction vessel and heated to 100 °C in an oven for 48 h. After the reaction was completed, the solution was washed three times with water and dried in a vacuum drying oven at 60 °C for 24 h to obtain a small amount of red crystals (Zn-PTZpy).

[0032] Example 4 The specific process for investigating the fluorescence properties of PTZpy and Zn-PTZpy is as follows: The fluorescence spectra of PTZpy and Zn-PTZpy were measured using steady-state fluorescence, respectively. The results are as follows: Figure 3 As shown, Figure 3 (a) and Figure 3 (b) shows the emission peaks of PTZpy and Zn-PTZpy at 520 nm and 516 nm and 594 nm, respectively. Zn-PTZpy may produce two different conformations under different aggregation states, resulting in two stable excited states and thus dual-emission fluorescence. Compared with the ligand, the steady-state solid-state fluorescence of the coordination polymer shows a significant red shift, which is attributed to the coordination of the ligand with the metal ion. Under UV excitation, PTZpy and Zn-PTZpy exhibit completely different emission colors. PTZpy shows cyan emission, while Zn-PTZpy shows orange-red emission. The CIE coordinates of the emission spectra of PTZpy and Zn-PTZpy are (0.374, 0.577) and (0.474, 0.470), respectively, corresponding to yellow and orange-red (…). Figure 3 c). To investigate the luminescent stability of Zn-PTZpy, the fluorescence decay curve of Zn-PTZpy was determined using transient fluorescence, as shown in the figure. Figure 3 As shown in d, the fluorescence lifetime of Zn-PTZpy is 0.87 ns.

[0033] Example 5 The specific process for investigating the fluorescence response of Zn-PTZpy prepared in Example 1 in common ions is as follows: (1) Add 2 mg Zn-PTZpy to 10 mL of water and sonicate for 60 min.

[0034] (2) Prepare solutions of different compounds (CO3) by mixing different types of anions. 2- SO4 2- OH - HPO4 2- AlO2 - SCN - S2O4 2- CO3 2-- H2PO2 - CrO4 2- (c = 1×10) -3 mol / L).

[0035] (3) Take 0.5 mL of anionic compound solution and add it to 4.5 mL of Zn-PTZpy solution for fluorescence testing.

[0036] (4) For fluorescence analysis, the excitation wavelength is set to 397 nm and the emission wavelength is collected from 417 to 700 nm; the excitation and emission slit widths are set to 3 nm and 3 nm, respectively.

[0037] The result is as follows Figure 4 The maximum emission wavelength of Zn-PTZpy appears at 495 nm. After adding different ions, it can be clearly seen that only S2O4 exhibits the highest emission wavelength. 2- This causes a significant enhancement in fluorescence; furthermore, only CrO4... 2- This causes significant fluorescence quenching. CN - SCN - HPO4 2- H2PO2 - OH - SO4 2- CO3 2- AlO2 - Under the same conditions, there was no significant effect on Zn-PTZpy. The fluorescence intensity of Zn-PTZpy at 497 nm was compared after titration with different ions. (S2O4) 2- The induced enhancement may reach over 200%, CrO4 2- The induced quenching degree can reach over 90%. Therefore, the above results indicate that Zn-PTZpy effectively quenches S2O4 in common ions. 2- and CrO4 2- It has good selectivity.

[0038] Example 6 Investigating the effect of Zn-PTZpy prepared in Example 1 on S2O4 2- and CrO4 2- The sensitivity of the detection is determined through the following process: S2O4 was added incrementally to 10 mL of aqueous solution of the complex Zn-PTZpy (2 mg / 10 mL). 2- and CrO4 2- Solution (c = 1 × 10) -3 Fluorescence was measured at mol / L, and the results are as follows: Figure 5 a, b, with S2O4 2- and CrO4 2- Gradually increase, (Zn-PTZpy+ S2O4) 2- The luminescence of the solution of (Zn-PTZpy+CrO4) is enhanced. 2- The luminescence of the solution is quenched. The luminescence efficiency is quantitatively described using the Stern-Volmer (SV) expression: I 0 / I =1+ K sv [M]. The quenching curve was observed by gradually increasing the concentration in the range of 0-200 μM. It exhibited a good linear quenching response at low concentrations. CrO4 was detected. 2- of K sv The value is 3.56 × 10 4 M -1 (Figure and diagram), the calculated LOD is 0.09 μM. For example... Figure 5 As shown in c and b, the S2O4 gradually increases in the range of 0-200 μM. 2- With increasing concentration, the fluorescence of Zn-PTZpy gradually increased, exhibiting a good linear response at low concentrations. Calculations yielded... K sv The value is 6.69 × 10 3 M -1 With an LOD of 0.12 μM, Zn-PTZpy can be used as a detector for S2O4. 2- and CrO4 2- A highly sensitive fluorescence sensor.

[0039] Comparative Example 1 To investigate the effect of different solvents on the present invention, this embodiment uses "THF" instead of "DMF" for preparation, and specifically includes the following steps: (1) Preparation of 3,7-bis(4-pyridyl)phenthiazine (PTZpy) ligand The process is exactly the same as step (1) in Example 1. (2) Preparation of zinc-based coordination polymer based on heterocyclic ligands (Zn-PTZpy) 0.05 mmol of 3,7-bis(4-pyridyl)phenthiazide (PTZpy) and 0.05 mmol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) were dissolved in THF (3 mL) and H2O (3 mL) and stirred for 10 min. The resulting solution was then transferred to a reaction vessel and placed in an oven to be heated to 120 °C for 24 h. After the reaction was completed, the product was a yellow solution and no solid product was obtained.

[0040] Therefore, it can be seen that changing the solvent (replacing DMF with THF) will not yield the zinc-based coordination polymer (Zn-PTZpy) based on heterocyclic ligands of this invention. This is because the carbonyl oxygen atom in the DMF molecule has a lone pair of electrons, which can interact with zinc ions (Zn... 2+ The zinc ion coordinates and occupies a coordination site, forming a "solvated" metal precursor. This process is relatively slow, which helps control the rate of crystal nucleation and growth, thus facilitating the formation of well-structured coordination polymer single crystals. While the oxygen atom in the THF molecule is also a potential coordination site, its coordination ability is much weaker than that of DMF. It cannot effectively form a stable intermediate with zinc ions, leading to an excessively fast reaction rate and the easy formation of amorphous precipitates, thus preventing the preparation of the target crystal Zn-PTZpy.

[0041] Comparative Example 2 To investigate the influence of the metal source on the present invention, this embodiment replaces "zinc nitrate hexahydrate" with "zinc chloride," specifically including the following steps: (1) Preparation of 3,7-bis(4-pyridyl)phenthiazine (PTZpy) ligand The process is exactly the same as step (1) in Example 1. (2) Preparation of zinc-based coordination polymer based on heterocyclic ligands (Zn-PTZpy) 0.05 mmol of 3,7-bis(4-pyridyl)phenthiazide (PTZpy) and 0.05 mmol of zinc chloride (ZnCl2) were dissolved in acetonitrile (3 mL) and H2O (3 mL) and stirred for 5 min. The resulting solution was then transferred to a reaction vessel and heated to 120 °C in an oven for 36 h. After the reaction was completed, the solution was washed three times with water and then dried in a vacuum drying oven at 60 °C for 24 h to obtain a yellow powder.

[0042] Therefore, it can be seen that replacing zinc nitrate hexahydrate with zinc chloride does not yield the heterocyclic ligand-based zinc coordination polymer (Zn-PTZpy) of this invention. This is because NO 3- It is a very weak coordinating anion that exists as an ion pair or very weakly coordinates to the metal center in a monodentate manner in solvents such as H2O or DMF. It is easily replaced by organic ligands (such as PTZpy).- With zinc ions Zn 2+ It has a strong coordination tendency, Cl - It will strongly occupy the coordination sites of zinc ions and compete with the organic ligand PTZpy for coordination with zinc ions.

[0043] Comparative Example 3 To investigate the effect of solvent ratio and dosage on the present invention, the following steps are specifically included: (1) Preparation of 3,7-bis(4-pyridyl)phenthiazine (PTZpy) ligand The process is exactly the same as step (1) in Example 1. (2) Preparation of zinc-based coordination polymer based on heterocyclic ligands (Zn-PTZpy) 0.025 mmol of 3,7-bis(4-pyridyl)phenthiazide (PTZpy) and 0.025 mmol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O) were dissolved in DMF (3 mL) and H2O (3 mL) and stirred for 5 min. The resulting solution was then transferred to a reaction vessel and heated to 100 °C in an oven for 48 h. After the reaction was completed, the solution was washed three times with water and dried in a vacuum drying oven at 60 °C for 24 h to obtain a small amount of flaky red crystals (Zn-PTZpy).

[0044] Therefore, changing the volume ratio of DNF to H2O from 3:1 to 3:3 does not yield the Zn-PTZpy heterocyclic ligand-based coordination polymer of this invention. This is because the significant increase in the water ratio leads to a substantial increase in the polarity of the entire solvent system and a greatly enhanced protonicity. The solubility of many heterocyclic aromatic ligands in strongly polar protic solvents (such as water) decreases drastically. The ligands may dissolve from a molecular state to a colloidal state, or even precipitate, failing to effectively encounter metal ions in solution and undergo ordered self-assembly.

[0045] The embodiments of this application have been described above with reference to the accompanying drawings. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the core ideas of this application. However, this application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of this application.

Claims

1. A method for preparing a zinc-based coordination polymer based on heterocyclic ligands, characterized in that, Includes the following steps: 3,7-Dibromo-10H-phenthiazide, pyridine-4-boronic acid and K2CO3 were dissolved in a mixture of DMF and H2O and stirred until homogeneous. Then tetra(triphenylphosphine)palladium was added and the mixture was heated under reflux under a protective gas. After the reaction was completed, the solvent was removed, impurities were separated and purified to obtain 3,7-di(4-pyridyl)phenthiazide. The 3,7-bis(4-pyridyl)phenthiazide and zinc nitrate hexahydrate were dissolved in a mixture of DMF and water, stirred until homogeneous, heated to react, washed and dried after the reaction was completed to obtain the zinc-based coordination polymer based on heterocyclic ligands.

2. The preparation method according to claim 1, characterized in that, The molar ratio of 3,7-dibromo-10H-phenthiazide, pyridine-4-boronic acid, tetrakis(triphenylphosphine)palladium and K2CO3 was 1.4 mmol: 11.2 mmol: 0.07 mmol: 20 mmol.

3. The preparation method according to claim 1, characterized in that, The molar ratio of the 3,7-bis(4-pyridyl)phenthiazide to zinc nitrate hexahydrate is 0.025 mmol: 0.02 mmol-0.03 mmol.

4. The preparation method according to claim 1, characterized in that, The heating reflux reaction is carried out at a temperature of 100℃-120℃ for a time of 48 h-72 h.

5. The preparation method according to claim 1, characterized in that, The heating reaction is carried out at a temperature of 100℃-110℃ for a duration of 24 h-48 h.

6. The preparation method according to claim 1, characterized in that, The volume ratio of DMF to H2O in the mixture is 3-8:

1.

7. The preparation method according to claim 1, characterized in that, The separation of impurities specifically includes the following steps: After the reaction is complete and the solvent is removed, the product is dissolved in a mixture of dichloromethane and water. The two phases are separated, the organic phase is washed, filtered, and rotary evaporated.

8. A zinc-based coordination polymer based on heterocyclic ligands, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.

9. A fluorescent probe, characterized in that, Including the zinc-based coordination polymer based on heterocyclic ligands as described in claim 8.

10. The heterocyclic ligand-based zinc-based coordination polymer of claim 8 or the fluorescent probe of claim 9 in the detection of S2O4 2- and CrO4 2- Applications in [the field].

Citation Information

Patent Citations

  • Preparation, structure and fluorescence property of trimesic acid zinc polymer

    CN106977748A

  • Compound and applications thereof, and organic electroluminescent device

    CN109535187A

  • Preparation method and application of copper cluster-phenothiazinyl metal organic framework with visible light catalysis C-N bond cross coupling performance

    CN119899395A

  • Zwitterionic zinc(II) carboxylate compounds and their use

    US20180057512A1

  • An efficient method for synthesis of 5-(3-pyridyl)-2,2'-bithiophene(sensitizer)

    WO2021019558A1